2017
DOI: 10.1681/asn.2017030353
|View full text |Cite
|
Sign up to set email alerts
|

GRHL2 Is Required for Collecting Duct Epithelial Barrier Function and Renal Osmoregulation

Abstract: Collecting ducts make up the distal-most tubular segments of the kidney, extending from the cortex, where they connect to the nephron proper, into the medulla, where they release urine into the renal pelvis. During water deprivation, body water preservation is ensured by the selective transepithelial reabsorption of water into the hypertonic medullary interstitium mediated by collecting ducts. The collecting duct epithelium forms tight junctions composed of barrier-enforcing claudins and exhibits a higher tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 77 publications
4
17
0
Order By: Relevance
“…The corticopapillary osmotic gradient perturbation of Epac1 null mice (Figures and ) resembled that reported in mice with genetically induced CD TJ ‘leakiness’ associated with less E‐cadherin expression . The striking CD clustering of mRNA coding for Avpr2, Epac1 and the downstream Epac1 target E‐cadherin (Table ) prompted a study of the CD junctions.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…The corticopapillary osmotic gradient perturbation of Epac1 null mice (Figures and ) resembled that reported in mice with genetically induced CD TJ ‘leakiness’ associated with less E‐cadherin expression . The striking CD clustering of mRNA coding for Avpr2, Epac1 and the downstream Epac1 target E‐cadherin (Table ) prompted a study of the CD junctions.…”
Section: Resultssupporting
confidence: 62%
“…Epac1 therefore appears to be required to maintain a steep medullary osmotic gradient to prevent water loss under antidiuretic conditions. A similar osmotic gradient deficiency was observed in mice with lowered CD paracellular TJ resistance due to CD‐specific deletion of the transcription factor GRHL2 . The similar decrease of Na + and osmolarity in the renal papilla and urine in GRHL2‐ and Epac1‐targeted mice ( and Figures and ), as compared to Wt mice, argues that water can equilibrate between the papillary tissue and the pre‐urine in the CD lumen.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…A recent study has demonstrated the importance of an intact epithelial barrier in the renal collecting duct for efficient water reabsorption [43]. Deletion of the transcriptional regulator Grainyhead-like 2 (Grhl2), an epithelial transcription factor that induces the expression of barrier-enforcing molecular TJ components including Cldn-4 [44], results in a leaky collecting duct epithelium and a decreased TER across the collecting duct epithelium.…”
Section: The Collecting Duct Epithelial Barrier In Electrolyte-free Wmentioning
confidence: 99%
“…Leakage of interstitial osmolytes across the Grhl2-deficient collecting duct epithelium is associated with defective retention of osmolytes in the interstitium of the inner medulla. Grhl2-deficient mice show signs of diabetes insipidus and fail to concentrate their urine adequately, although AQP-mediated water transport across the apical and basolateral membranes of Grhl2-deficient collecting ducts is intact [43]. This indicates that a tight collecting duct epithelial barrier is crucial for the maintenance of osmolality gradients and for effective collecting duct water reabsorption.…”
Section: The Collecting Duct Epithelial Barrier In Electrolyte-free Wmentioning
confidence: 99%